THU0603 Performance of The 2013 American College of Rheumatology/european League against Rheumatism Systemic Sclerosis Classification Criteria. (15th July 2016) - Gheorghiu, A.M.; Dobrota, R.; Predescu, T.; Grigorescu, L.; Soare, A.; Gorga, M.; Ionitescu, R.; Jurcut, R.; Magda, S.; Constantinescu, T.; Sfrenţ-Cornăţeanu, R.; Bojinca, M.; et al.
Abstract : Background: Systemic sclerosis (ScS) is a polymorphic autoimmune disease, with increased morbidity and mortality, often diagnosed in advanced stages. The recently published 2013 American College Of Rheumatology/European League Against Rheumatism (ACR/EULAR) classification criteria for SSc were developed to increase the identification of early/mild SSc patients. Objectives: To compare the sensitivity and specificity of the 2013 ACR/EULAR criteria with 1980 ACR criteria in a single-centre cohort of patients with SSc, diagnosed according to expert oppinion. Methods: Data of SSc patients evaluated in our EUSTAR centre between 2004–2015 have been retrospectively analyzed. The control cohort included patients with Raynaud's phenomenon of other ethiology than SSc, evaluated between 2009–2015. The sensitivity and specificity of the 2013 ACR/EULAR and 1980 ACR criteria were tested using the McNemar test for correlated proportions. Results: One hundred and fifty one patients with SSc (90.1% women, mean±SD age 58.4±13.2 years) and 65 controls (87.7% women, mean±SD age 43.7±14.6 years) were included. The sensitivity of the 2013 ACR/EULAR and 1980 ACR criteria were 94.7% and 84.4%, respectively (p<0.001). The specificity of the 2013 ACR/EULAR and 1980 ACR criteria were 86.2% and 96.9%, respectively (p=0.01). Patients missclassified according to the new 2013 ACR/EULAR criteria were 17, whereas according to the old 1980 ACR criteria were 32. The sensitivity of the 2013ACR/EULAR was significantly better than the 1980 ACR criteria in the limited cutaneous SSc patients (93.1 vs. 82.2%, p<0.001). Conclusions: The 2013 ACR/EULAR criteria have a better sensitivity and missclassify fewer patients than the 1980 ACR criteria. Their excelent performance is close to the gold standard of diagnosis in SSc (expert opinion). Acknowledgement: * This abstract was realized as part of the "Development of a computer-based nailfold videocapillaroscopy (NVC) system for longitudinal evaluation of patients with systemic sclerosis" (QUANTICAP) project, financed by the UEFIS-CDI PN-II-PT-PCCA-2013–4-1589 grant. Disclosure of Interest: None declared